Performance evaluation of gas-power strategies for building energy conservation. (15th March 2015) - Gabbar, Hossam A.; Runge, Jason; Bondarenko, Daniel; Bower, Lowell; Pandya, Devarsh; Musharavati, Farayi; Pokharel, Shaligram
Highlights: Comparison of natural gas and hydrogen fuels for energy conservation in buildings. Comparison between hydrogen and natural gas fuel cell is performed. Simulations of building energy supply. Performance evaluation of two potential gas-power supply scenarios in buildings. Natural gas fuel cell showed better performance over hydrogen fuel cell. Abstract: The work provided herein involves a comparison of natural gas and hydrogen fuels for the purpose of energy conservation for buildings via alternative energy generation methodologies. A case study simulation was developed for an average type of commercial building, a nine storey hotel located in Toronto. The two alternative energy source case studies involved the generation of hydrogen via the wind turbine for the fuel cell, and the use of natural gas directly in the steam reforming fuel cell. The simulations for both scenarios were run and the recorded results were compared to the original case study, as well as between the scenarios. To supply for the base load of the building the fuel cells were given the same kW rating for both scenarios. The identification of all existing technologies for hydrogen gas and natural gas has been carried out, and the similar technologies between the two gases were found. For the purpose of realism, only existing purchasable technologies were considered in this paper. Due to the lack of commercially available technologies for hydrogen gas, only a comparison of fuel cell systems could be accomplished. Over the course of the investigative work it was found that when there is no direct supply of hydrogen to the site of utilization, the natural gas fuel cell is beneficial to the building due to its greater efficiency and lower cost. The major drawback for the hydrogen gas fuel cell, when the on-site generation is involved, is that no thermal power extraction systems currently exist for purchase and utilization in the buildings.